Strategi Ekspositori Guru PAI dalam Menguatkan Akhlakul Karimah Siswa di SMP IT Al-Istiqomah Global School - Muhammad Iqbal Baskara; Ajat Rukajat; Khalid Ramadhani (AS-SABIQUN, 2022)
This research is motivated by the many cases in the classroom such as calling fellow friends by the name of their parents, sleeping during class hours, joking excessively so that learning is a little disturbed. This type of research is a field research (Field Research), using qualitative research methods. Presentation of data is done descriptively through data collection techniques with interviews, observations, and documentation. Data analysis uses data reduction, data presentation, and data verification. This study aims to find out how the strategy of Islamic Religious Education teachers in strengthening students' Akhlakul Karimah, the process of inculcating Akhlakul Karimah behavior and what are the supporting and inhibiting factors in order to strengthen students' Akhlakul Karimah at SMP IT Al-Istiqomah Global School. In this study, it contains the expository strategy of Islamic Religious Education teachers in the post-covid-19 pandemic in order to strengthen students' Akhlakul Karimah, the expository strategy here is carried out by explaining first about the moral material then students discussing and the teacher will give an example of the moral material. In order to strengthen Akhlakul Karimah students in schools are also supported by existing programs in schools such as Mabit, LDKS, Qur'an Camp and Social Service which can support in order to strengthen Akhlakul Karimah Students so that cases that occur in schools can be reduced even though it has not been 100 % as expected.